Investigation into local cell mechanics by atomic force microscopy mapping and optical tweezer vertical indentation. (18th December 2015) - Coceano, G; Yousafzai, M S; Ma, W; Ndoye, F; Venturelli, L; Hussain, I; Bonin, S; Niemela, J; Scoles, G; Cojoc, D; Ferrari, E
Abstract: Investigating the mechanical properties of cells could reveal a potential source of label-free markers of cancer progression, based on measurable viscoelastic parameters. The Young's modulus has proved to be the most thoroughly studied so far, however, even for the same cell type, the elastic modulus reported in different studies spans a wide range of values, mainly due to the application of different experimental conditions. This complicates the reliable use of elasticity for the mechanical phenotyping of cells. Here we combine two complementary techniques, atomic force microscopy (AFM) and optical tweezer microscopy (OTM), providing a comprehensive mechanical comparison of three human breast cell lines: normal myoepithelial (HBL-100), luminal breast cancer (MCF-7) and basal breast cancer (MDA-MB-231) cells. The elastic modulus was measured locally by AFM and OTM on single cells, using similar indentation approaches but different measurement parameters. Peak force tapping AFM was employed at nanonewton forces and high loading rates to draw a viscoelastic map of each cell and the results indicated that the region on top of the nucleus provided the most meaningful results. OTM was employed at those locations at piconewton forces and low loading rates, to measure the elastic modulus in a real elastic regime and rule out the contribution of viscous forces typical of AFM. When measured by either AFM or OTM, the cell lines' elasticity trend was similar for the aggressive MDA-MB-231 cells, which were found to be significantly softer than the other two cell types in both measurements. However, when comparing HBL-100 and MCF-7 cells, we found significant differences only when using OTM.